2015
DOI: 10.1002/app.42331
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear pyrolysis layer model for thermal behavior of nonhomogeneous charring materials

Abstract: To improve the performance of charring materials as the thermal protection system in supersonic vehicles subjected to aerodynamic heating, we develop a nonlinear pyrolysis layer model of nonhomogeneous charring composites, propose a scheme of variable density in which the resin distribution of charring materials is taken as a piecewise linear function, and then simulate the thermal behavior of the design by means of the written calculation codes. This model reveals that the thermal behavior of charring materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, this model does not take into account the real situation between the virgin layer and the char layer, because the density and the enthalpy of pyrolysis gas change with heating time in this stage. In order to analyze the effect of this stage on ablation, Li et al [21,22] established a one-dimensional ablation model including the virgin layer, the pyrolysis layer, the char layer and the ablation layer and the effect of density on ablation was analyzed. It was found that not only external heat flux, moving interfaces and boundary affect the ablation result, but the change in density also affects the ablation, it was shown that the pyrolysis layer is essential in the one-dimensional ablation model.…”
Section: Introductionmentioning
confidence: 99%
“…However, this model does not take into account the real situation between the virgin layer and the char layer, because the density and the enthalpy of pyrolysis gas change with heating time in this stage. In order to analyze the effect of this stage on ablation, Li et al [21,22] established a one-dimensional ablation model including the virgin layer, the pyrolysis layer, the char layer and the ablation layer and the effect of density on ablation was analyzed. It was found that not only external heat flux, moving interfaces and boundary affect the ablation result, but the change in density also affects the ablation, it was shown that the pyrolysis layer is essential in the one-dimensional ablation model.…”
Section: Introductionmentioning
confidence: 99%
“…6 Thermochemo-mechanical phenomenon used in the ablation process dissipates the high heat fluxes by serial endothermic processes in the material and releases gaseous products. [7][8][9] The pyrolytic gasses flow in the direction of the exposed surface through the formed porous and charred solid material. 5,8 At a certain point of heating, the walls of pores become so thin that the exterior layer of the material is split off under the action of external flow pressure (external mechanical erosion) or pores break down by the release of pyrolytic gases (internal mechanical erosion).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical reaction that takes place at 3000 K and above is called sublimation. 9,10 This is a highly endothermic phenomenon, but normally the composite wall does not reach the sublimation temperature and so the chemical reaction with flow gasses is the main chemical ablation contribute. 6 Ablation chart of composite material is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The pyrolysis of charring ablation materials and the flow of pyrolysis gases in the material can bring off amounts of heat [4][5][6][7]. Meanwhile, the char on the material surface usually ablates because it reacts with the oxygen in the boundary layer behind the shock wave.…”
Section: Introductionmentioning
confidence: 99%